Pengaruh Brand Image, Brand Trust Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Frestea - Ahmad Rian Buchory; Andriansyah Bachtillah Putra (Jurnal Manajemen Bisnis Era Digital, 2024)
This research aims to analyze the influence of Brand Image, Brand Trust and Product Quality on Purchase Decisions for Frestea products. The subjects in this research were consumers who had previously purchased Frestea products. The sample used in this research was 160 respondents. The sampling technique uses purposive sampling using a quantitative descriptive approach. The data analysis used is Smart PLS. The research results show that Brand Image has a positive and significant effect on Purchasing Decisions, Brand Trust has a positive and significant effect on Purchasing Decisions and Product Quality has a positive and significant effect on Purchasing Decisions. Partially, the results obtained are that there is a significant positive influence on Brand Image on Purchasing Decisions, Brand Trust has a positive and significant influence on Purchasing Decisions and Product Quality has a positive and significant influence on Purchasing Decisions